PROTECTIVE EFFECT OF VITAMIN E ON ACETAMINOPHEN–INDUCED HYPERLIPIDEMIA IN FEMALE RABBITS - Al-Jowari, Suha (Iraqi Journal of Science, 2024)
The protective effect of vitamin E against acetaminophen (paracetamol) inducedhyperlipidemia in female rabbits was tested. Twenty female rabbits were randomlydivided into four groups (five animals in each group). The first group was dosedwith acetaminophen at 200 mg/kg (BW). The second group was dosed with 50mg/kg. BW of vitamin E and the third group was treated with 200 mg/kg (BW) ofacetaminophen and 50 mg/kg (BW) of vitamin E, while the last was administeredwith distilled water and considered as a control group. These animals were orallydosed using a micropipette for 14 days.The results showed that there was a significant (P<0.05) increase in serumcholesterol, triglycerides, low-density lipoprotein (LDL), very low-densitylipoprotein (VLDL) concentrations and atherosclerosis index except high-densitylipoprotein (HDL) which decreased significantly in the treated group withacetaminophen compared with the control group. On the other hand, these abovementionedparameters decreased significantly (P<0.05) except HDL concentration inthe group treated with vitamin E compared with the control group. Concerning theanimals treated with acetaminophen and vitamin E, the results also showed thatthese above mentioned parameters decreased significantly (P<0.05) except HDLconcentration compared with the group treated with acetaminophen and nosignificant (P0.05) difference in the above mentioned parameters compared withthe control group.In conclusion, the antioxidant vitamin E may reduce the oxidative modification ofLDL by acetaminophen and may be used as a therapeutic agent in preventing thedevelopment and progression of atherosclerosis.